PERANCANGAN SISTEM KEAMANAN JARINGAN BERBASIS VLAN, FIREWALL, DAN PORT SECURITY MENGGUNAKAN MIKROTIK CISCO - Sendy Kurniawan; Ade Setiawan (Jurnal Komunikasi, 2025)
The rapid development of information technology has made computer Networks a vital component for communication and data exchange in organizations, including PT Jasa Raharja Putera. However, Networks without proper Security mechanisms are highly vulnerable to both internal and external threats. This study aims to design a Network Security system by implementing Firewall, Port Security, and VLAN to enhance Network protection at the Marketing Office of PT Jasa Raharja Putera. The research methodology consists of field observations, interviews, literature review, and Network simulation using GNS3 software. The proposed design utilizes a Mikrotik Router for routing and firewall functions, Cisco manageable switches for VLAN segmentation and Port Security, and Access Point configurations on each floor. A Layer 7 Protocol-based firewall is applied to restrict non- productive website access within the employee VLAN, while the head office computer is granted full access through MAC Address filtering. The simulation results indicate that the proposed design improves Network Security by isolating traffic between VLANs, preventing unauthorized devices, and filtering internet traffic. Therefore, this design can serve as a practical reference for developing secure and structured Network infrastructures in similar office environments